Screening for antenatal depression in women attending the Chris Hani Baragwanath academic hospital antenatal clinic - Maisto, Alexandra Stephanie (My University, 2019)
BACKGROUND: Antenatal Depression is very common in South Africa, resulting in a significant burden to those affected and potentially resulting in long term negative outcomes for their children. Multiple associated risk factors exist amongst the vulnerable socio-economically disadvantaged population. Screening for antenatal depression and associated risk factors may assist with the identification of cases and in the development of treatment interventions that serve to alleviate the burden. Interventions need to be population specific in order to be effective. Further South African studies are required to determine the prevalence and determine region specific risk factors. AIMS: To establish the prevalence of depressive symptoms and describe the associated socio-demographic features in a sample of women attending the Antenatal clinic at Chris Hani Baragwanath Hospital. OBJECTIVES: To screen for antenatal depression, using the EPDS in the antenatal clinic at the Chris Hani Baragwanath Hospital. To describe the results of the screening and demographic factors and compare biographical information and a positive screen on the EPDS to establish associations, and to describe the attitude of these women towards information and treatment options for depression. METHODS: A cross sectional and descriptive research design was used. Primipara and multipara pregnant women were recruited from the CHBAH antenatal clinic. The interview consisted of a biographical questionnaire, review of the antenatal card as well as completion of the EPDS. The prevalence of depressive symptoms were calculated, as determined by EPDS cut off scores of 13 or greater and 10 or greater, together with their 95% confidence intervals. The Relative Risks for an elevated EPDS score (of 13 or greater) for each significant risk factor was determined using binomial regression RESULTS: 32% of the sample had a score of greater than 10 on the EPDS and 23,5% scored greater than 13. There were strong associations between certain variables: not having tertiary education (RR 0.46; 95% CI 0.23-0.90), an unwanted pregnancy (RR 2.78; 95% CI 1.89-4.07) and the presence of life stressors during pregnancy (RR 2.03; 95% CI 1.39-2.96). Most participants favoured treatment at their local clinic; individual talk therapy (51.9%) was the first choice of treatment and only 23,8% would accept medication as an option. CONCLUSIONS: Antenatal depression is highly prevalent in South Africa. The detection of associated factors is important in determining high-risk groups for targeted interventions can be put in place. Screening should be introduced into routine antenatal care to improve the pick up rate of depressive symptoms in women at risk and population specific, accepted, targeted interventions be put in place.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand Medical School, Johannesburg, in partial fulfilment of the requirements for the degree Masters of Medicine in the branch of Psychiatry. Johannesburg, 2019